Critical analyzed information of International Air Transport Association (Divulgation paper) (Nexo Revista Científica, 2021)
The International Air Transport Association aims at representing the airline industry by enhancing awareness about the benefits of airlines to the national economies, and in this way, improving decision making regarding airline activities. Integrity is an important value if at all member airlines are expected to have trust in the organization’s duty to protect their interest. The main benefit that airlines can gain in joining IATA is the ability to be adequately represented by an organization whose voice in the industry is powerful. Member airlines are also assured of financial success as IATA recommends best practices that should be implemented in order to uphold safety, environmental sustainability, and efficient processes. Ultimately, IATA’s role in championing for the rights of airlines has been influential, and the improved performance in the industry is evidence that the association’s efforts have been fruitful.